2020
DOI: 10.1007/s11684-020-0801-x
|View full text |Cite
|
Sign up to set email alerts
|

The role played by traditional Chinese medicine in preventing and treating COVID-19 in China

Abstract: Traditional Chinese medicine (TCM), an ancient system of alternative medicine, played an active role in the prevention and control of COVID-19 in China. It improved the clinical symptoms of patients, reduced the mortality rate, improved the recovery rate, and effectively relieved the operating pressure on the national medical system during critical conditions. In light of the current global pandemic, TCM-related measures might open up a new channel in the control of COVID-19 in other countries and regions. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 8 publications
0
75
0
Order By: Relevance
“…The results of a meta-analysis of 16 papers, including 1335 cases of sepsis in a Chinese population, showed that, compared with ulinastatin alone, the combination of Xuebijing with ulinastatin led to a shorter mechanical ventilation time, shorter ICU stay, improved 28-day survival rate, reduced incidence of MODS and mortality, decreased procalcitonin concentration, ameliorated acute physiology and chronic health evaluation (APACHE) II score, and reduced levels of TNF-α and IL-6 ( 94 ). Xuebijing also exhibited antithrombotic activity, which could prevent vascular embolism caused by COVID-19 ( 91 ). Xuebijing has been recommended for the treatment of severe COVID-19 in China ( 51 ).…”
Section: Immunotherapy Strategies For Patients With Critically Ill Comentioning
confidence: 99%
“…The results of a meta-analysis of 16 papers, including 1335 cases of sepsis in a Chinese population, showed that, compared with ulinastatin alone, the combination of Xuebijing with ulinastatin led to a shorter mechanical ventilation time, shorter ICU stay, improved 28-day survival rate, reduced incidence of MODS and mortality, decreased procalcitonin concentration, ameliorated acute physiology and chronic health evaluation (APACHE) II score, and reduced levels of TNF-α and IL-6 ( 94 ). Xuebijing also exhibited antithrombotic activity, which could prevent vascular embolism caused by COVID-19 ( 91 ). Xuebijing has been recommended for the treatment of severe COVID-19 in China ( 51 ).…”
Section: Immunotherapy Strategies For Patients With Critically Ill Comentioning
confidence: 99%
“…Symptomatic support therapy and comprehensive interventions are mainly used in clinical practice (Wu et al, 2020b). Since the outbreak of COVID-19 (Wu et al, 2020b), TCM has been able to get involved in the whole process of treatment and achieved remarkable results (Li et al, 2020). TCM integrates its treatment principles (syndrome differentiation and threeconcerned therapy of "individual concerned therapy, environment concerned therapy, climate concerned therapy") (Wu et al, 2020a) with the different stages of COVID-19.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, based on the composition of the MXSGT, the Qing Fei Pai Du Decoction (QFPDD) and Lianhua Qingwen Capsules (LHQWC) were manufactured and issued by the National Health Commission and have been widely used in China to treat the COVID-19 patients. Data has suggested significant positive clinical outcomes [18] , [19] , [20] , [21] .…”
Section: Resultsmentioning
confidence: 99%